Series-Resonant DC-DC Converter for Solar Photovoltaic Non Isolated Applications - Arredondo J. (2019)
This paper analyzes a Dual Active Bridge seriesresonant DC-DC converter for solar photovoltaic DC microgrid. These converters are particularly attracted for renewable energy applications due to high switching frequency with low switching losses. The analysis is composed of the equivalent circuit using Fourier series. Besides, the steady-state response is shown where the current flow depends only on the phase shift modulation. MPPT algorithm is designed and discussed. Finally, the simulations results using the PSIM software for a 500 W prototype are shown. © 2019 IEEE.